1999
DOI: 10.1093/emboj/18.20.5601
|View full text |Cite
|
Sign up to set email alerts
|

p38 MAP kinase is required for STAT1 serine phosphorylation and transcriptional activation induced by interferons

Abstract: 2 ) is a prerequisite for the formation of the transcription factor complex interferon-stimulated gene factor 3 (ISGF3) in response to interferon-α (IFN-α). Here we show that p38 mitogen-activated protein kinase (MAPK), an activator of cPLA 2 , is essential for both IFN-α and IFN-γ signalling. SB203580, a specific inhibitor of p38, was found to inhibit ISGF3 formation but had no apparent effects on signal transducer and activator of transcription (STAT)1 homodimer formation. Regardless of this, the antiviral a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
270
1
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 341 publications
(295 citation statements)
references
References 40 publications
23
270
1
1
Order By: Relevance
“…Consistent with previous results [46,47], Stat1a was strongly phosphorylated on Ser727 by IFN-a (Fig. 7B, lane 2, %phosphoserine/Stat1a: 69.0 AE 1.9).…”
Section: Influenza a Virus Inhibits Ifn-a-induced Tyrosine And Serinesupporting
confidence: 92%
“…Consistent with previous results [46,47], Stat1a was strongly phosphorylated on Ser727 by IFN-a (Fig. 7B, lane 2, %phosphoserine/Stat1a: 69.0 AE 1.9).…”
Section: Influenza a Virus Inhibits Ifn-a-induced Tyrosine And Serinesupporting
confidence: 92%
“…Phosphorylations of STAT1 and STAT3 at the Tyr701 or Tyr705 residues, respectively, induce their dimerization, nuclear translocation, and DNA binding [6,17]. In our study, IL-27 alone induced tyrosine phosphorylation of STAT1 (Fig.…”
Section: Expression Of Il-12 Il-23 and Il-27 Receptor Subunits In Hsupporting
confidence: 58%
“…IL-12, IL-23, and IL-27 activate JAK2 and TYK2, and IL-27 simultaneously activates JAK1 JAK catalyze the tyrosine phosphorylation of STAT [2,17] and are constitutively associated with cytokine receptors. Ligand binding to the receptors induces dimerization or oligomerization of receptor subunits and allows juxtaposition, activation, and autoor cross-phosphorylation of the associated JAK [2,17,18].…”
Section: Expression Of Il-12 Il-23 and Il-27 Receptor Subunits In Hmentioning
confidence: 99%
See 1 more Smart Citation
“…Fish IFN exerts its multiple functions, at least antiviral action, through a JAK -STAT pathway. In mammals, apart from the JAK -STAT signal transduction pathway, additional pathways of signal transduction, possibly involving the RNA-dependent protein kinase (PKR) [58], mitogen-activated protein kinase [59,60], and phosphatidylinositol 3-kinase [61], may also be operative under some circumstances. We have also cloned PKR gene and TLR3 gene that are activated by ds RNA [62], and demonstrated that they are also expressed in response to ds RNA virus GCHV [26].…”
Section: Discussionmentioning
confidence: 99%